h(-2)=-2+9

Simple and best practice solution for h(-2)=-2+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h(-2)=-2+9 equation:



h(-2)=-2+9
We move all terms to the left:
h(-2)-(-2+9)=0
We add all the numbers together, and all the variables
h(-2)-7=0
We multiply parentheses
-2h-7=0
We move all terms containing h to the left, all other terms to the right
-2h=7
h=7/-2
h=-3+1/2

See similar equations:

| (0-1)=6(p–8)–12 | | w÷2=9 | | x+6+7x=6 | | x/50=1 | | w−68=25 | | 2x-19=8+3x | | s+8=19 | | 5+5-8x=26 | | 4/3x-3=33 | | x+5+5x=11 | | 3.7+10m=6.46 | | -24+2x=36+7x | | 12=-3/7(x) | | 8(x-1)=6x+3 | | 4x-52=11x+123 | | -x/11=-3 | | x^2-11x=18=0 | | 11=5(x-30 | | x/13=-3 | | 4(x-3)=-3x | | -x-111=-10x+114 | | 84.78=3.14*r^2*9 | | 10k–1=k–43 | | r/4=7/5​ | | -1/4x+5=3 | | -192-2x=51+7x | | 2(5x+8)=5(3x-17)+16 | | -3(c+)-4c=60 | | -2+x/3=4 | | -6(x+3)=-18 | | -74-3x=-7x+26 | | -53=-8x+3 |

Equations solver categories